Sex Predictability by Using Mandibular Canine Index - Atreya, Alok; Shrestha, Rijen; Tuladhar, Lujaw Ratna; Nepal, Samata; Shrestha, Raju; Sah, Sanjay Kumar (Journal of Nepal Health Research Council, 2020)
Background: Canines are known for their higher resistance to trauma and pathological alterations when compared to other teeth. Among all the teeth, canines show highest sexual dimorphism.Methods: This descriptive cross-sectional study was commenced from January 2019 to April 2019 after the ethical approval from Institutional Review Committee. The maximum mesio-distal widths of right and left mandibular canines and mandibular inter-canine arch width were measured on the cast with the help of a divider and digital vernier callipers. Mandibular canine index was calculated by dividing the mesio-distal width of each mandibular canine with inter-canine arch width. Data was entered and analyzed using Statistical Package for the Social Sciences version 21. Results: Sex predictability by using mandibular canine index in the present study showed poor sex predictability (57.5% - 62.5%).Conclusions: Sex determination should be done by other methods and mandibular canine index should be used cautiously in Nepalese population.Keywords: Canine dimorphism; forensic anthropology; forensic dentistry; forensic identification, sex determination.